A diverging Europe on the edge. The independent Annual Growth Survey - iAGS 2015 (Paris, 2014)
"This is the third independent Annual Growth Survey (iAGS), each a response to the European Commission's AGS, and we have to take note sadly of the continuation of the crisis. Response to the euro sovereign debt crisis has been substantial, but we analyse that it was not sufficient to give a strong enough momentum to the euro area economy in order lastingly to exit the recession it entered 6 years ago. Failing to exit the crisis brings many poisons, economic, social, and political. Unemployment is at high levels, inequality is rising, and convergence between European regions that was once the rule is no longer occurring. Pressure on wages and the need to restore internal balances between countries fuels deflation. Debt deleveraging, private or public, is far from accomplished and the prospect of falling prices may be the mechanism by which stagnation is perpetuated. The European project of a prosperous and inclusive society is giing to sink if we fail to rebound."